2021
DOI: 10.1111/apt.16448
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pregnancy outcomes in women with inflammatory bowel disease treated with thiopurines and/or anti‐TNF: a French nationwide study 2010–2018

Abstract: Summary Background Data about thiopurines or anti‐TNF use during pregnancy in women with inflammatory bowel diseases (IBD) are reassuring. However, many studies are based upon small sample sizes. Aims To assess IBD medication safety during pregnancy. Methods Using the French national health database, which covers more than 99% of the French population, around 65 000 000 people, we identified pregnancies ending with a birth in IBD patients in France between 2010 and 2018. Pregnancy outcomes (vital status at bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…Mean gestational age and neonatal birth weight were similar between POIBD and non-POIBD patients [ 7 ]. Uncontrolled IBD during pregnancy has been associated with preterm labor and low birth weight [ 8 ]. Since treatment adherence has been shown to be low in the pediatric IBD population [ 9 ], it is imperative that physicians counsel patients and families about the importance of treatment, as lower disease activity during pregnancy is associated with better outcomes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mean gestational age and neonatal birth weight were similar between POIBD and non-POIBD patients [ 7 ]. Uncontrolled IBD during pregnancy has been associated with preterm labor and low birth weight [ 8 ]. Since treatment adherence has been shown to be low in the pediatric IBD population [ 9 ], it is imperative that physicians counsel patients and families about the importance of treatment, as lower disease activity during pregnancy is associated with better outcomes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A percentage of 9–18% of women with IBD are at risk of preterm birth, compared to the general population (5–9% risk of premature birth). The risk is elevated in both UC and CD patients and especially high in patients with active disease [ 107 , 108 ]. Cornish et al showed that the risk is twice as high in mothers with CD compared to the control group [ 106 ].…”
Section: Impact Of Ibd On Pregnancymentioning
confidence: 99%
“…A recent large French nationwide study reported an association between thiopurine monotherapy and stillbirth, preterm births, and large for gestational age compared with pregnancies exposed to anti-TNF or no medications (62). Thiopurine exposure in the setting of combination therapy with an anti-TNF therapy was also associated with preterm births and large for gestational age (62). This association with adverse fetal outcomes, albeit a different study design, was not seen in the PIANO study (61).…”
Section: Medicationsmentioning
confidence: 99%